2021
DOI: 10.5194/acp-21-4615-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the variability in vertical separation between biomass burning aerosols and marine stratocumulus on cloud microphysical properties over the Southeast Atlantic

Abstract: Abstract. Marine stratocumulus cloud properties over the Southeast Atlantic Ocean are impacted by contact between above-cloud biomass burning aerosols and cloud tops. Different vertical separations (0 to 2000 m) between the aerosol layer and cloud tops were observed on six research flights in September 2016 during the NASA ObseRvations of Aerosols above CLouds and their intEractionS (ORACLES) field campaign. There were 30 contact profiles, where an aerosol layer with aerosol concentration (Na) > 500 cm−3 wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 87 publications
(92 reference statements)
3
17
0
Order By: Relevance
“…Three important factors affecting So were discussed (Sorooshian et al, 2019): above-cloud Na, below-cloud Na, and 650 meteorological conditions. This study analyzed ORACLES data from all three IOPs and the first two conclusions were consistent with the analysis of ORACLES 2016 (Gupta et al, 2021). Future work will compare in situ data with Rp retrievals from the Airborne Precipitation Radar (Dzambo et al, 2021) to evaluate the sensitivity of So to the use of satellite retrievals of Rp (Bai et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Three important factors affecting So were discussed (Sorooshian et al, 2019): above-cloud Na, below-cloud Na, and 650 meteorological conditions. This study analyzed ORACLES data from all three IOPs and the first two conclusions were consistent with the analysis of ORACLES 2016 (Gupta et al, 2021). Future work will compare in situ data with Rp retrievals from the Airborne Precipitation Radar (Dzambo et al, 2021) to evaluate the sensitivity of So to the use of satellite retrievals of Rp (Bai et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…The above-cloud aerosol plume was associated with elevated water vapor content which influenced cloud-top humidity and dynamics following the mechanisms discussed by Ackerman et al (2004). 115 During the 2016 IOP, variable vertical displacement (0 to 2000 m) was observed between above-cloud aerosols and the MSC (Gupta et al, 2021;hereafter G21). Instances of contact and separation between the aerosol and cloud layers were associated with differences in the aboveand below-cloud Na, water vapor mixing ratio (wv), and cloud-top entrainment processes.…”
mentioning
confidence: 95%
“…Stratocumulus clouds (Sc hereafter) are the dominant cloud type over Earth's subtropical oceans. Significant advances in our understanding of subtropical Sc have been documented in many previous studies including their typical cloud fractions (Stephens et al, 2012;King et al, 2013;, radiative impacts (Hang et al, 2019), and associated precipitation processes using data from past field experiments (Stevens et al, 2003), long-term ground-based data collection (Mann et al, 2014;Yang et al, 2018), and spaceborne remote sensors (Fox and Illingworth, 1997;L'Ecuyer and Stephens, 2002;Lebsock et al, 2011;Chen et al, 2011;Lebsock et al, 2011;Werner and Deneke, 2020). Despite these advances, until recently observations of cloud and precipitation processes over the Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…Results so far have shown that smoke from southern African biomass burning is often found within the remote southeast Atlantic boundary layer (Zuidema et al, 2018) and can have important radiative (Zhang and Zuidema, 2019) and microphysical (Gupta et al, 2021) effects. Important caveats have also been identified, including that methods that relate cloud properties to above-cloud rather than below-cloud aerosol concentrations likely misrepresent aerosol microphysical effects on clouds (Diamond et al, 2018); that at high smoke concentrations, clouds move from an aerosol-limited to an updraft-limited regime in which cloud sensitivity to further aerosol increases is limited (Kacarab et al, 2020); and that some of the lowest aerosol concentrations observed at Ascension Island occur during the biomass burning season, likely due to in-cloud scavenging (Pennypacker et al, 2020).…”
Section: Field Campaigns Targeting Firesmentioning
confidence: 99%